The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jso.26244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KRAS status on tumor response and survival after neoadjuvant treatment of locally advanced rectal cancer

Abstract: Background: Mutation of the KRAS oncogene (mKRAS) in colorectal cancer has been associated with aggressive tumor biology, resistance to epidermal growth factor inhibitors, and decreased overall survival (OS). The aim of the current study was to analyze the association of mKRAS with pathologic complete response (pCR) and neoadjuvant rectal (NAR) score, and its impact on the survival of patients with locally advanced rectal cancer who were managed with multimodality therapy. Methods: The National Cancer Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“… 148 However, a large retrospective study including 1886 patients with UICC stage II–III and a systematic review both failed to confirm the relationship between KRAS mutation and decreased rates of pCR. 150 , 151 Noteworthy, the systematic review did not discriminate between different genotypes of KRAS mutations, 151 while Duldulao et al 149 found that KRAS mutations in different codons resulted in a differential resistance profile to nCRT. In particular, rectal cancers with KRAS codon 13 and G12V mutations were reported to less likely exhibit a pCR.…”
Section: Introductionmentioning
confidence: 99%
“… 148 However, a large retrospective study including 1886 patients with UICC stage II–III and a systematic review both failed to confirm the relationship between KRAS mutation and decreased rates of pCR. 150 , 151 Noteworthy, the systematic review did not discriminate between different genotypes of KRAS mutations, 151 while Duldulao et al 149 found that KRAS mutations in different codons resulted in a differential resistance profile to nCRT. In particular, rectal cancers with KRAS codon 13 and G12V mutations were reported to less likely exhibit a pCR.…”
Section: Introductionmentioning
confidence: 99%
“…For example, wild-type KRAS patients were more likely to show pCR than those with any KRAS mutation (p = 0.006), while KRAS codon 13 mutations were negatively associated with pCR (p = 0.03). Nevertheless, the role of KRAS mutation in predicting the response to nCRT is still controversial [38]. TP53 mutation was reported to be associated with radioresistance, while patients with both TP53 and KRAS mutations were more likely to show less response to nCRT and to suffer lymph node metastasis [39,40].…”
Section: Gene Mutationsmentioning
confidence: 99%
“…Between 30 and 40% of patients with colorectal cancer carry the KRAS mutation (80). In LARC, the KRAS mutation has been associated with tumor invasion and metastasis, insensitivity to epidermal growth factor inhibitor and low overall survival time (81,82). Certain patients with LARC have low sensitivity to NCRT, and have side effects to radiotherapy and chemotherapy, such as trisomy, radiation proctitis and sexual dysfunction.…”
Section: Mri-based Radiomics To Predict Kras Mutationmentioning
confidence: 99%
“…At present, there are numerous studies investigating the association between the KRAS mutation and treatment response following NCRT. For example, Zhou et al (82) retrospectively analyzed 1,886 patients with LARC, and found that the KRAS mutation was not associated with low PCR rate and tumor degradation following neoadjuvant treatment of LARC; however, the KRAS mutation was associated with low survival rate following NCRT, suggesting a poor prognosis. In another study, Peng et al (85) retrospectively analyzed 70 patients with LARC who received NCRT prior to surgery at the Cancer Center of Sun Yat-Sen University (Guangzhou, China).…”
Section: Mri-based Radiomics To Predict Kras Mutationmentioning
confidence: 99%